Intestinal Microbiota And Diet in IBS: Causes, Consequences, or Epiphenomena?. (February 2015) - Rajilić‐Stojanović, Mirjana; Jonkers, Daisy M; Salonen, Anne; Hanevik, Kurt; Raes, Jeroen; Jalanka, Jonna; de Vos, Willem M; Manichanh, Chaysavanh; Golic, Natasa; Enck, Paul; Philippou, Elena; Iraqi, Fuad A; et al.
Abstract : N/A: Irritable bowel syndrome (IBS) is a heterogeneous functional disorder with a multifactorial etiology that involves the interplay of both host and environmental factors. Among environmental factors relevant for IBS etiology, the diet stands out given that the majority of IBS patients report their symptoms to be triggered by meals or specific foods. The diet provides substrates for microbial fermentation, and, as the composition of the intestinal microbiota is disturbed in IBS patients, the link between diet, microbiota composition, and microbial fermentation products might have an essential role in IBS etiology. In this review, we summarize current evidence regarding the impact of diet and the intestinal microbiota on IBS symptoms, as well as the reported interactions between diet and the microbiota composition. On the basis of the existing data, we suggest pathways (mechanisms) by which diet components, via the microbial fermentation, could trigger IBS symptoms. Finally, this review provides recommendations for future studies that would enable elucidation of the role of diet and microbiota and how these factors may be (inter)related in the pathophysiology of IBS.